2019
DOI: 10.1097/inf.0000000000002259
|View full text |Cite
|
Sign up to set email alerts
|

Augmented ILT3/LILRB4 Expression of Peripheral Blood Antibody Secreting Cells in the Acute Phase of Kawasaki Disease

Abstract: Background: Kawasaki disease (KD) is an acute, systemic vasculitis syndrome that occurs in children. The clinical symptoms and epidemiologic features of KD strongly suggest that KD is triggered by unidentified infectious agents in genetically predisposed patients. In addition, a number of studies have described the role of B cells in the development of KD. To obtain a mechanistic insight into the humoral immune response of B-lineage cells in KD patients, we examined peripheral blood antibody secret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…26 A study demonstrated the frequency of CD19 + CD27 hi ASCs was dramatically increased in acute phase of Kawasaki disease (KD). 27 Ashenafi et al also revealed a greater proportion of circulating plasmablasts (PB), which is CD3 − CD19 + CD20 − CD27 hi CD38 hi , was found in adult participants with active TB. 28 In contrast, Sealy et al showed that ASCs were fractionally reduced, but nonetheless observed in respiratory tract tissues in the absence of eosinophils by evaluating virus-specific responses 1 month and 4 months following an intranasal virus infection of eosinophil-null mice.…”
Section: Discussionmentioning
confidence: 94%
“…26 A study demonstrated the frequency of CD19 + CD27 hi ASCs was dramatically increased in acute phase of Kawasaki disease (KD). 27 Ashenafi et al also revealed a greater proportion of circulating plasmablasts (PB), which is CD3 − CD19 + CD20 − CD27 hi CD38 hi , was found in adult participants with active TB. 28 In contrast, Sealy et al showed that ASCs were fractionally reduced, but nonetheless observed in respiratory tract tissues in the absence of eosinophils by evaluating virus-specific responses 1 month and 4 months following an intranasal virus infection of eosinophil-null mice.…”
Section: Discussionmentioning
confidence: 94%
“…Together, these findings reveal that LILRB4 creates an immunosuppressive microenvironment, thereby decreasing its antitumor efficacy. LILRB4 expression is upregulated under pathological conditions, such as Kawasaki disease, systemic lupus erythematosus, sepsis, and mental illness, in addition to tumors ( 71 ). CRD alters several cell-autonomous mechanisms to induce tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Jensen et al revealed that ILT3 loss of function polymorphism was associated with the increase of inflammatory cytokine level in SLE [42]. In addition to SLE, LILRB4 is also associated with a variety of immune diseases, such as Kawasaki disease [43] and allergic diseases [18]. LILRB4 is also closely related to diseases of other systems.…”
Section: Relationship With Diseasementioning
confidence: 99%